Informiranost kot ključno vodilo do kakovosti življenja pacientov s stomo - Štemberger Kolnik, Tamara (Obzornik zdravstvene nege, 2009)
Introduction: An ostomy, especially a permanent one, will have an impact on the quality of life of patients as it affects also their body image and self-esteem. Therefore, properpre-operative and post-operative counselling, expert care and support can significantly contribute to improvement in the quality of their lives. Aim: The goal of the research was to determine in which phase of the treatment process the stoma patients receive enough information on their condition and when the information is not sufficient. The research was designed to assess also the contribution of health care providers in their better coping with all aspects of stoma management. Method: A questionnaire was designed to obtain quantitative data on the above issues from the patients and the enterostomal therapists in Slovenia. Results: The research results show that expert advice and counselling on stoma management is mainly provided by enterostomal therapists during hospital stay. However, the primary health care providers often lack the necessary knowledge and competence for the work with patients requiring stomal therapy. The quality of information given is generally influenced by the "cognitive understanding of information" and the "psychological needs of the patient". Discussion and conclusions: Heath education of stoma patients as well as relevant education of health professionals in relation to stoma is of significance in physical and psychological aspects of stoma management at all levels of care.
Keywords: communication; informiranje; kakovost življenja; komuniciranje; pacienti; standard of living; stoma